Correction Of Glucose-6-Phosphate Dehydrogenase (G6PD) Viangchan Mutation In Monocytes Using CRISPR/CAS9 - Vengidasan, Lelamekala (2018)
G6PD deficiency is one of the most common enzymopathy in human with approximately 400 million people affected worldwide. Two hundred seventeen types of mutations have been described so far with some mutations are life threating. G6PD deficiency has also been linked to various types of cancers, tumours and metabolic diseases. This study aimed to correct G6PD deficiency by using CRISPR/Cas9 system. In this study, G6PD Viangchan as used; a type of mutation which is common in Malaysian Malays. G6PD Viangchan has cloned into pET26b (+) expression plasmid and expressed in BL21 (DE3) system.